Investigation of novel photosensitisers for photodynamic cancer therapy - Paszko, Edyta (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
Photodynamic therapy (PDT) has developed over last century and is now becoming a more widely used medical tool having gained regulatory approval for the treatment of various diseases such as cancer and macular degeneration. It is based on photochemical reactions between light and tumour tissue with exogenous photosensitising agents (PS), most often porphyrins. Photochemical reactions lead to the conversion of molecular oxygen (3O2) into singlet oxygen (1O2) which is a key cytotoxic agent that damages cells.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin